Effect of Solvent pH on Antioxidant and Phytochemical Activities of Mulhatti Aerial Parts (Glycyrrhiza glabra L.) - Parvesh, Devi; Sushila, Singh; Seema, Sangwan; Sheetal, Sihag; Promila,; Ritu, (Journal of Antioxidant Activity, 2021)
Medicinal plants have been used since the era of Vedic history for their health care system where herbal medicine has a long history of use. It is also a very popular medicinal plant belonging to the Leguminosae family and is commonly known as Mulhatti. It contains phytochemicals such as flavonoids, triterpene saponins and other constituents such as coumarins, sugars, amino acids, tannins, starch, choline, phytosterols etc. The present study was conducted for the estimation of phytochemicals (total phenols and flavonoids) and the evaluation of the total antioxidant capacity and DPPH free-radical scavenging activity in aqueous extracts of different pH (2, 4, 7 and 9) from aerial parts of Glycyrrhiza glabra L. The content of phenolic compounds was maximal at pH 7 (14.13 mg GAE/g) and flavonoids at pH 9 (4.90 mg CE/g) and the total antioxidant capacity was maximal at pH 9 (13.43 mg AAE/g) and free radical scavenging DPPH activity was highest at pH 7 (IC50 value = 60.48 µg/ml). Thus, the aerial part is a good source of phytochemicals and also acts as a good antioxidant.
Keywords: Glycyrrhiza glabra; Leguminosae; free radical scavenging activity and total antioxidant capacity.